Treating Antibiotic Resistance Genes in Proteus Spp. were Isolated from Renal Stone Patients by Crataegus rhipidophylla and Adiantum capillus - Ali Mohammed, Srwa; Abdul Aziz Hama Ali, Mohammed; Lattif Mohammed, Dereh (Kurdistan Journal of Applied Research, 2018)
Nine isolates of Proteus spp. were isolated from 100 urine samples of renal stone patients which were the urine specimens obtained directly from Sulaimani Teaching Hospital Laboratory, and identified according to the cultural characteristic, morphological, biochemical examination. The antibiotic susceptibility test for all isolates were conducted to nine antimicrobial agents including (Ciprofloxacin (Cip), Tetracycline(TE), Neomycin (N), Gentamicin (CN), Erythromycin (E), Nitrofurantoin (F), Naldixic acid (NA), Imipenem (IPM), Amoxicillin (AX). Plasmid analysis of these isolates showed presence are (22) Kb plasmid. Curing of antibiotic resistance genes by using methanol extracts for leave of Crataegus rhipidophylla and Adiantum capillus was performed. The minimum inhibitory concentration of these medicinal plants through methanol extracts which were 5000 µg/ml and 1000 µg/ml for Ailanthus altissima and Adiantum capillus respectively. The Sub minimum inhibition concentration (SMIC) was also determined. The results of transformation and curing experiments revealed that SMIC of Ailanthus altissima extract was cured or eliminated plasmid completely, and (SMIC) of Adiantum capillus was cured (CN, E, and AX) resistant genes.